Non-places of memory: Barcelona 1888-1929 - Gil Poisa, María (Ángulo Recto. Revista de estudios sobre la ciudad como espacio plural, 2013)
Non-places and places of memory are constant presences in the life of every city, witness of the history and the identity of the space and its inhabitants. In this work I want to show how the spaces of Montjuic and the Ciutadella, both of them places with a strong symbolic burden for the city of Barcelona, have a fundamental role for the collective memory of people from Barcelona as spaces for pain and, in the same way, places for transition, relief and appreciation.